A Bis(silylene)‐Substituted ortho‐Carborane as a Superior Ligand in the Nickel‐Catalyzed Amination of Arenes. Issue 41 (15th September 2016) - Zhou, Yu‐Peng; Raoufmoghaddam, Saeed; Szilvási, Tibor; Driess, Matthias
Abstract: The synthesis and structure of the first 1, 2‐bis(NHSi)‐substituted ortho ‐carborane [(LSi:)C]2 B10 H10 (termed SiCCSi) is reported (NHSi= N ‐heterocyclic silylene; L=PhC(NtBu)2 ). Its suitability to serve as a reliable bis(silylene) chelating ligand for transition metals is demonstrated by the formation of [SiCCSi]NiBr2 and [SiCCSi]Ni(CO)2 complexes. The CO stretching vibration modes of the latter indicate that the Si II atoms in the SiCCSi ligand are even stronger σ donors than the P III atoms in phosphines and C II atoms in N ‐heterocyclic carbene (NHC) ligands. Moreover, the strong donor character of the [SiCCSi] ligand enables [SiCCSi]NiBr2 to act as an outstanding precatalyst (0.5 mol % loading) in the catalytic aminations of arenes, surpassing the activity of previously known molecular Ni‐based precatalysts (1–10 mol %). Abstract : The right bite : A chelating bis‐N‐heterocyclic silylene ligand bridged by an o ‐carborane (SiCCSi) and its corresponding Ni complexes (see example) were synthesized, fully characterized, and successfully applied in Ni‐catalyzed Buchwald–Hartwig coupling reactions. [SiCCSi]NiBr2 is the most active precatalyst for this transformation that has been reported to date.